2016
DOI: 10.1002/ece3.2327
|View full text |Cite
|
Sign up to set email alerts
|

Life history evolution and cellular mechanisms associated with increased size in high‐altitude Drosophila

Abstract: Understanding the physiological and genetic basis of growth and body size variation has wide‐ranging implications, from cancer and metabolic disease to the genetics of complex traits. We examined the evolution of body and wing size in high‐altitude Drosophila melanogaster from Ethiopia, flies with larger size than any previously known population. Specifically, we sought to identify life history characteristics and cellular mechanisms that may have facilitated size evolution. We found that the large‐bodied Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 76 publications
5
40
0
Order By: Relevance
“…Although not as well-studied as latitudinal clines, numerous phenotypic traits in animals, including Drosophila, exhibit altitudinal clines [26]. In this study we measured the wake-sleep patterns of D. melanogaster derived from natural populations captured at different altitudes from tropical regions of sub-Saharan Africa [23, 24, 2729] (Additional file 1: Table S1). Over a wide range of temperatures D. melanogaster from high altitudes show a less robust mid-day siesta that is characterized by more fragmented sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Although not as well-studied as latitudinal clines, numerous phenotypic traits in animals, including Drosophila, exhibit altitudinal clines [26]. In this study we measured the wake-sleep patterns of D. melanogaster derived from natural populations captured at different altitudes from tropical regions of sub-Saharan Africa [23, 24, 2729] (Additional file 1: Table S1). Over a wide range of temperatures D. melanogaster from high altitudes show a less robust mid-day siesta that is characterized by more fragmented sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the more pronounced apical expansion of cells is not a general feature of D. suzukii development, but rather seems to be specific to its ovipositor. It has been suggested that a common mechanism for cell size expansion is polyploidy (29), which can be measured using nuclear size (30). However, in both species, we find no increase in nuclear area from 48 to 54 h APF (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…Thus what has been lacking for studies testing evolutionary models of canalization is a model system with the relevant natural history that can be studied in a multivariate perspective. Lack et al (2016a), among other recent studies, demonstrated that populations of Drosophila melanogaster from sub-Saharan Africa recently adapted to a high-altitude environment via increased body size and wing morphology, among other traits (Pitchers et al, 2013; Lack et al, 2016a,b; Bastide et al, 2016; Fabian et al, 2015; Klepsatel et al, 2014). Intriguingly, the high-altitude population show a substantial increase in the frequency of qualitative mutational defects of wing morphology (Lack et al, 2016a).…”
Section: Introductionmentioning
confidence: 88%
“…Drosophila melanogaster strains used in the current study represent a subset of those from Lack et al (2016a,b). The high-altitude inbred strains were derived from flies collected in Fiche, Ethiopia at an altitude of 3070 m in December 2011.…”
Section: Methodsmentioning
confidence: 99%